Chinese myths & legends legends of the universe, deities and heroes - Chen Lianshan; Zhang Fengru; Chen Shanshan (Beijing China Intercontinental Press, 2016)
The author believes that ancient Chinese myths and legends were gradually formed on the basis of those of the Huaxia (Han) and by absorbing from the Dongyi (ancient eastern tribes) and the Miaoman (ancient Southern tribes). The author sorted materials from various ancient Chinese books and records, and arranged the myths in order to aid readers' appreciation of the materials. In some chapters, he compares Chinese myths with western ones (especially in the Greek).
Preface --- The origin of the universe : I. Chaos ; II. The beginning of the world -- The Origin of Mankind: I. The image of Nuwa ; II. The creator of human beings ; III. Nuwa mending the heaven ; IV. Nuwa and marriage ; V. The end of Nuwa -- Universe in myth : I. The heaven and earth ; II. Ten suns and twelve moons ; III. Mount Kunlun,city of deities on earth ; IV. Deities' world in the sea ; V. Capital of ghost and Taodu Mountain -- Fuxi,the god of east heaven ; I. The birth of Fuxi ; II. Fuxi and Nuwa: human creator and goddess of marriage ; III. Cultural civilization of Fuxi ; IV. Fuxi,the god of east heaven -- Yandi,the god of south heaven : I. The contribution of Emperor Yandi ; II. Later generations of Emperor Yandi ; III. Chaos in the Emperor Yandi's era -- Emperor Huangdi,the god of central heaven : I. The birth of Emperor Huangdi ; II. The war Between Emperor Huangdi and Emperor Yandi ; III. War between Emperor Huangdi and Chiyou ; IV. Xingtian scrambles for the throne ; V. Daily life of the central God Huangdi ; VI. Contributions of Emperor Huangdi and his subordinates -- Shaohao,the god of west heaven and Zhuanxu,the god of north heaven : I. Shaohao in Chinese myth ; II. Birth of Zhuanxu ; III. Cutting off the link between heaven and earth ; IV. War Between Zhuanxu and Gonggong ; V. The origin of the Mengshuangshi tribe ; VI. The end of Zhuanxu ; VII. The offspring of Zhuanxu -- Myths in the era of Emperor Diku : I. Diku and his five wives ; II. The conflict between Ebo and Shichen ; III. Ebo steals fire ; IV. Diku's daughters -- Myths & legends in the era of Yao : I. The birth of Yao ; II. Miracles in Yao's rule ; III. Miracle judge Gaoyao ; IV. Ten suns in the sky and the severe drought ; V. Yi shot suns ; VI. Yi and Luoshen's love affairs ; VII. The legend of Hebo's wedding ; VIII. Chang'e flying to the moon ; IX. Gun tamed the raging waters ; X. Emperor Yao's demise -- Myths & legends in the era of Shun : I. Birth of Shun and his youth ; II. Shun ascends to the throne ; III. Buried at the Jiuyi Mountain -- Myths & legends in the era of Dayu : I. The birth of Dayu ; II. Orders to control the floodwater ; III. Dayu's tragedy of marriage ; IV. Having all the rivers under control -- Other myths & legends : I. Kuafu chasing the sun ; II. Yugong moving mountains ; III. Cowboy and Vega -- Appendix : major characters in Chinese myths & legends -- Appendix : chronological table of the Chinese dynasties
Cultural China series : The first volume
Keywords: Mythology, Chinese; Legends -- China; Folklore -- China